PENGELOLAAN RUANG DAN FURNITUR MEMPENGARUHI REHABILITASI DAN PEMBENTUKAN PERILAKU POSITIF ANAK BINAAN DI LPKA KELAS 1 TANGERANG - Refranisa; Sujito, Ahmad Deryant Permana (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
This study investigates the impact of spatial and behavioral mapping at the Class 1 Juvenile Correctional Institution (LPKA) in Tangerang using a behavior setting approach. The research stems from the importance of physical environmental arrangements in supporting rehabilitation programs for children involved in the justice system. LPKA, which is specifically designed to foster the development and rehabilitation of juveniles, includes physical elements such as building layout, cleanliness, and facility quality that influence the habits and behaviors of the inmates. The aim of this study is to identify how physical conditions and spatial arrangements affect the behavior of juveniles at LPKA Class 1 Tangerang. Using a qualitative method, the study involved direct observation at the institution to map the space and analyze the children’s interactions with their environment. The analysis shows that suboptimal spatial arrangements, such as limited areas and poor maintenance of cleanliness, can affect juvenile behavior, including the emergence of aggressive habits and difficulties in social adaptation. These findings provide recommendations for LPKA management to improve facilities and spatial organization in order to create a more conducive environment for the rehabilitation process. This research emphasizes that spatial mapping based on the principles of behavior setting can be an important strategy in identifying and encouraging positive habits among juveniles in LPKA. The results are expected to serve as a reference for LPKA management policies to enhance the effectiveness of rehabilitation programs.